Enhanced Detection of Protein in Urine by Droplet Evaporation on a Superhydrophobic Plastic. Issue 1 (8th July 2014) - McLane, Jolie; Wu, Chun; Khine, Michelle
<x xml:space="preserve">Abstract</x> Protein in urine can be detected using a simple colorimetric output by evaporating droplets on a superhydrophobic (SH) surface. Evaporation on a SH surface allows fluid to dramatically concentrate; the weak surface adhesion allows the droplet of fluid to constantly decrease its footprint area and contact diameter. On a SH surface, pure water completely evaporates. Molecules in solution, however, are confined to a footprint that is 8.5 times smaller than the original and are greatly concentrated. By concentrating molecules, a 160 times improved detection sensitivity is achieved compared to controls. With the low‐cost fabrication method and simple technique, highly sensitive detection can be achieved in a low‐cost platform. Utility is demonstrated by detecting protein in urine in the pre‐eclampsia range (150–300 μgmL−1) for pregnant women.